THEORETICAL FOUNDATIONS FOR THE TRAINING OF ORAL TRANSLATORS - Fayziyeva Gulrukh (Academia Science Repository, 2023)
This article is about the organization of the process of training simultaneous interpreters in our country and the requirements for them.